2022
DOI: 10.3390/polym14132558
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the High-Temperature and Rheological Properties for Asphalt Sealant Modified by SBS and Rubber Crumb

Abstract: Crack sealing is an important measure for pavement maintenance. Hot-poured crack sealant is the most utilized material for crack sealing. However, its poor high-temperature and rheological properties seriously weaken the mechanical properties of repaired pavement. Thus, to overcome the disadvantage of the poor high-temperature and rheological properties of sealant, styrene–butadiene–styrene (SBS) and rubber crumb (CR) were utilized for modifying the asphalt-based sealants. Softening point tests, temperature te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…The temperature sweep test also showed that the asphalt binders modified with SBS and CR had higher flexibility at high temperatures. When considering the shear modulus and phase angle of asphalt binders, the viscoelastic balance of the 20% CR and 5% SBS-modified asphalt binder was more suitable for dealing with cracking issues [80]. The higher Superpave values for rutting resistance and complex modulus in the frequency sweeps produced better rheological performance with higher CR contents.…”
Section: Rheological Propertiesmentioning
confidence: 99%
“…The temperature sweep test also showed that the asphalt binders modified with SBS and CR had higher flexibility at high temperatures. When considering the shear modulus and phase angle of asphalt binders, the viscoelastic balance of the 20% CR and 5% SBS-modified asphalt binder was more suitable for dealing with cracking issues [80]. The higher Superpave values for rutting resistance and complex modulus in the frequency sweeps produced better rheological performance with higher CR contents.…”
Section: Rheological Propertiesmentioning
confidence: 99%
“…A study also showed that waste tire rubber powder (WTR) exists in a granular state in asphalt, which is not conducive to the compatibility of the two, resulting in stress concentration. At present, using WTR composite with other asphalt modifiers is the mainstream way to prepare a modified asphalt with better performance, including common modified materials such as SBS, PE, EVA, and so on [6][7][8][9]. Although composite-modified asphalt prepared using WTR and SBS has excellent performance at high and low temperatures, there are some problems, the most important of which is the presence of rubber molecular chains and the difference in physicochemical properties with asphalt, resulting in high viscosity in the modified asphalt, processing difficulties, high temperature degradation, poor storage stability, hydrogen sulfide gas release processing [3,4], and mixture mixing difficulties [2,5].…”
Section: Introductionmentioning
confidence: 99%
“…During road use, cracks are affected by factors such as temperature, precipitation, and loading. Cracks can develop into frost swelling and mineral spalling during stretching, destroying the structural integrity and service life of roads [1][2][3][4]. Therefore, the timely repair of cracks is very significant.…”
Section: Introductionmentioning
confidence: 99%